Pembelajaran Mandiri Seni Tari Melalui Konten Youtube sebagai Inovasi Pembelajaran Masa Kini - Fahmida Yuga Pangestika; Setyo Yanuartuti (Universitas Negeri Medan, 2020)
This paper aims to analyze the response of connoisseurs through independent learning through Ombyak Trimurti Dance through Youtube content that serves to hone dance skills and get to know other regional arts. Ombyak Trimurti dance uploaded by the channel of the Department of Tourism and Culture of East Java Province ‘Culture and Art’ is a creative dance originating from Ponorogo Regency, with its proud achievements, the dance received a positive response from elementary school to high school students. This makes researchers who are also the stylists of the Ombyak Trimurti dance very important to appreciate the responses of appreciators or students. Youtube content as an 'Learning Resource for Art' by presenting dance videos can do independent learning with mimicking or observing techniques. This study uses a qualitative approach and is supported by data in the form of dance videos that emphasize independent learning outcomes through imitation techniques. The conclusion of this study is the independent learning of dance through YouTube content which is the response of the community as connoisseurs of dance art from various circles provides inspiration that learning can be done anywhere with any learning resources and the presence of Youtube content is able to provide new insights and knowledge that is to know the special arts from other regions.